UPAYA BAWASLU KABUPATEN PROBOLINGGO MENINGKATKAN PERAN SERTA MAHASISWADALAM PENGAWASAN PARTISIPATIF - Aprilia, Violeta Dwi; Rohim, Abdur (JUSTNESS - Jurnal Hukun dan Agama, 2024)
Abstrack Election Supervisory Board (Bawaslu) as a trusted body of guardians in holding democratic, dignified, and quality elections. Bawaslu or the General Election Supervisory Agency is an election organizing agency in charge of supervising the implementation of elections in all regions of the Unitary State of the Republic of Indonesia. The vision of the General Election Supervisory Agency (Bawaslu) is the realization of the General Bawaslu's role is very important because it aims to create an election with integrity in accordance with the rules of the election. The purpose of this research is to find out how important the role of students in the election and what are the efforts of the Probolinggo Regency General Election Supervisory Agency (Bawaslu) in increasing the role of students in participatory supervision. This research method uses an empirical research method with an approach through interviews and looking at existing data to the staff and commissioners of Bawaslu Probolinggo Regency. With this research, we hope that there will be an understanding regarding the duties and authorities of Bawaslu and the role of students who should be to oversee future elections and elections. The results of this study concluded that the role of students is very important in participatory supervision for future elections and elections. To avoid unwanted things in the implementation of the election, the Bawaslu of Probolinggo Regency has contributed to providing education to increase the Human Resources (HR) of students related to the election. With the role of students, it is expected to minimize all forms of violations in every stage in the Elections and Elections. With the synergy between the Bawaslu of Probolinggo Regency and students, it is hoped that there will be an increase in the progress of democracy in Indonesia. Keyword : Effort, Bawaslu, Role, University Student.